A Qualitative Study on the Role of Music in Enhancing Divergent Thinking and Creative Writing in High School Students - Liu, He (Pacific International Journal, 2025)
This study explores the integration of music into creative writing pedagogy to enhance divergent thinking and narrative expression among high school students. Grounded in the theoretical frameworks of Guilford and Torrance, and supported by findings in cognitive neuroscience, the research examines how selected Gott Tanzte by E Nomine and The Castle by Nobuo Uematsu affect students’ ideation, emotional engagement, and narrative structure. Using a qualitative approach, in-depth interviews were conducted with ten students across three secondary schools in Xiamen, China. Findings revealed that music functioned as a cognitive and emotional catalyst, stimulating fluency, flexibility, and originality in student writing. Students reported more vivid imagery, emotionally expressive content, and coherent narrative structures, with music often serving as both inspiration and organizational guide. Some challenges were noted, particularly in revision phases, highlighting the need for flexible, personalized application. These results suggest that music can be a powerful pedagogical tool for fostering creativity, emotional literacy, and student motivation in writing classrooms. Implications for differentiated instruction and curriculum design are also discussed.